Multiple Stent Delivery System "Multi-LOC": Focal self-expanding nitinol stenting of complex femoropopliteal lesions—A monocenter feasibility pilot study. (January 2019) - Sigl, Martin; Jung, Johannes; Kölble, Heinz; Amendt, Klaus
Aims: The Multiple Stent Delivery System (VascuFlex® Multi-LOC) is a novel stent delivery system with six short stents (13 mm long each) mounted on one wire-guided catheter, designed for the treatment of femoropopliteal arteries. The aim of the present study is to evaluate the safety and the feasibility of the VascuFlex® "Multi-LOC" stent delivery system, which enables spot stenting without changing the delivery system. Methods and results: After proof of concept in a porcine model and after European Conformity marking, first clinical experiences were gathered in 20 patients with severe intermittent claudication or critical limb ischemia. First-in-human data are presented. The study included 20 limbs that underwent femoropopliteal revascularization for claudication (n = 14) or critical limb ischemia (n = 6). "Multi-LOC" provisional spot stenting resulted in acute technical success in all lesions with resolution of flow-limiting dissection and elastic recoil after balloon dilatation of the femoropopliteal artery. There were no device-related complications. Follow-up examinations after 30 to 40 days revealed no major adverse events, and six months' results were encouraging. Conclusions: First clinical use of the novel Multiple Stent Delivery System (Multi-LOC) after balloon dilatation of the femoropopliteal artery was safe and feasible in this early study.